1973
DOI: 10.1073/pnas.70.3.954
|View full text |Cite
|
Sign up to set email alerts
|

Development of Locomotor Patterns in the Absence of Peripheral Sense Organs and Muscles

Abstract: The role of peripheral sense organs and muscles in specifying the circuitry of the central nervous system during ontogeny was tested in larval lobsters. Presumptive locomotor appendages, the abdominal swimmerets, were extirpated before their differentiation. Electrophysiological recordings made 2-4 weeks later from the corresponding motor nerves showed that, despite the absence of the target muscles and sense organs, normal reflexes and normal patterns of rhythmic locomotor output appeared in the swimmeret mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1973
1973
1992
1992

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Similar developmental questions are posed by the other behaviour patterns which appear for the first time in stage IV. The ontogeny of the swimmeret system has been studied by Davis (Davis 1973;Davis & Davis 1973), and its particular relation to larval exopodite beating is considered in the present study . Also is strikingly different in larval and post-larval lobsters (figure 8) and it may be possible to interpret this difference in terms of the developing action of the various types of motor element which have been shown to control tail flexion in the adult Macrura (Bowerman & Larimer 1974;Larimer, Eggleston, Masukawa & Kennedy 1971;Schrameck 1970;Wiersma 1938;Wine & Krasne 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Similar developmental questions are posed by the other behaviour patterns which appear for the first time in stage IV. The ontogeny of the swimmeret system has been studied by Davis (Davis 1973;Davis & Davis 1973), and its particular relation to larval exopodite beating is considered in the present study . Also is strikingly different in larval and post-larval lobsters (figure 8) and it may be possible to interpret this difference in terms of the developing action of the various types of motor element which have been shown to control tail flexion in the adult Macrura (Bowerman & Larimer 1974;Larimer, Eggleston, Masukawa & Kennedy 1971;Schrameck 1970;Wiersma 1938;Wine & Krasne 1972).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that motor neurone firing patterns for cricket song (Bentley & Hoy, 1974) lobster swimmerett beating (Davis, 1973) and locust flight (Kutsch, 1974) develop normally in the absence of sensory feed-back. These results combined with the well known stereotypy of behaviour among invertebrates and the demonstration of genetic control of motoneurone firing patterns (Bentley & Hoy, 1974) have supported the view that the development of normal function in the invertebrate nervous system is independent of experience.…”
Section: Discussionmentioning
confidence: 99%
“…The study is intrinsically interesting as an analysis of a swimming behaviour in an animal with a relatively rigid body that locomotes by beating appendages serially. Because the analysis was conducted on a developing system through several stages it provides new information about behavioural development and, in association with previous work (Davis 1973(Davis , 1974Davis & Davis 1973), poses further questions in that area. The developmental aspect of the study is dealt with further in the third paper .…”
Section: Hgammarus (Swimming)mentioning
confidence: 99%
“…In the lobster, H o m a m s, it has also proved possible to examine swimmeret beating activ in the early developmental stages (Davis 1974), and Davis and his colleagues have produced evidence that the motor patterning responsible for swimmeret beating, which appears first in stage IV of development, is present in the central abdominal ganglia in the absence of prior sensory input from the swimmerets (Davis 1973;Davis & Davis 1973). Although swimmeret beating does not start until stage IV, it is not the first rhythmic activity of the larva.…”
Section: ) •mentioning
confidence: 99%
See 1 more Smart Citation